Neuroprotective effect of Annona squamosa & (-) Anonaine in decreased GABA receptor of epileptic rats - Mayur Porwal, Arvind Kumar (Journal of Applied Pharmaceutical Science, 2015)
Annona squamosa and its active alkaloid content (-) Anonaine are known for antiepileptic activity on the basis of literature review. The objective of this study was to establish neuroprotection by Annona squamosa and its active alkaloid content (-) Anonaine as an antiepileptic agent by acting on GABA receptor. For neuroprotective assessment, variations of GABA, GABAA, GABAB receptors in the cortex region of the brain in epileptic rats and potential applications of Annona squamosa and its isolated chemical constituent (Anonaine) were investigated by using confocal microscopy. Nootropic activity in epileptic rats was also studied by radial and Y-maze model. GABA receptor binding analysis in the cortex region of epileptic rats showed significant decrease in Bmax (p
Keywords: Neuroprotective, Annona squamosa, anonaine, GABA, epilepsy, Confocal microscopy.